2003
DOI: 10.1002/bjs.4007
|View full text |Cite
|
Sign up to set email alerts
|

Risk of dysplasia in the columnar cuff after stapled restorative proctocolectomy

Abstract: Background: Stapled restorative proctocolectomy (SRP) for ulcerative colitis retains a 'cuff ' of columnar epithelium, which carries a risk of undergoing malignant change. The risk of neoplastic transformation was studied in a series of patients who underwent SRP for ulcerative colitis. Methods:One hundred and thirty-five patients who underwent SRP for ulcerative colitis between 1988 and 1998 were followed up by cuff surveillance biopsy. The median follow-up was 56 (range 12-145) months and the median time sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 24 publications
1
44
1
Order By: Relevance
“…Their mean age was 45 years . The mean length of hospital stay was 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) days. Twenty two (63%) were treated due to FAP, 12 (34%) for colon tumor or polyp with concomitant rectum cancer and 1 (3%) for severe dysplasia in ulcerative colitis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their mean age was 45 years . The mean length of hospital stay was 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) days. Twenty two (63%) were treated due to FAP, 12 (34%) for colon tumor or polyp with concomitant rectum cancer and 1 (3%) for severe dysplasia in ulcerative colitis.…”
Section: Resultsmentioning
confidence: 99%
“…Once it was identified that the anal transition site immediately above the dentate line contributed to incontinence, the requirement for mucosectomy started to be questioned (10). However, a site with cancer is left behind if a rectum wall of more than 1.5-2 cm remains in place (11). In our clinic, our cases routinely undergo mucosectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, any residual rectal mucosa is subject to persistent inflammation caused by ulcerative colitis (cuffitis) as well as the risk of colitisassociated dysplasia and carcinoma, particularly in patients with dysplasia or carcinoma in the resected colon. [6][7][8][9] A rectal mucosectomy may alleviate this somewhat, but in our experience, any colonic/rectal mucosa left behind by such a procedure (or when a mucosectomy is not performed) can interdigitate with the now-adjacent ileal mucosa as the anastomosis matures to create a histological 'hybrid' mucosa that can be difficult to recognize as definitively colonic or enteric under the microscope. Furthermore, the ileal pouch mucosa undergoes a variety of histological and functional changes and is subject to a nonspecific inflammatory reaction known as 'pouchitis', an idiopathic phenomenon that can lead to pain, diarrhea, and bleeding when severe.…”
mentioning
confidence: 90%
“…The main type of reconstruction after colectomy can be broadly divided into the straight ileo-anal anastomosis (SIAA) and the creation of a reservoir from an ileal pouch. The use of a pouch has become increasingly more popular because it appears to reduce the frequency of stooling [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%